Table of Content - - (Journal of Curriculum and Teaching Methodology, 2024)
Table of Content: 1. The degree to which social studies teachers in the South Al Sharqiyah Governorate in the Sultanate of Oman possess the skills of employing artificial intelligence in education Fahad Salem Saif Almasrouri 2. The level of teaching practices among Arabic language teachers for the intermediate stage in light of the sustainable development goals in Makkah Al-Mukarramah Dr. Mashael Saleh Al-Dosari, Noura Abdullah Al-Zahrani 3. A Proposal for Developing the Textbook of Hadith and Islamic Education for First Grade in Secondary Schools in Saudi Arabia Fahad Odeh Awad Alatwi, Dr. Iman Mohamed Mabrouk Qutb 4. The reality of including the dimensions of digital citizenship in the courses of my eternal language in the intermediate stage in the Kingdom of Saudi Arabia Dr. Mashael Saleh Al-Dosari, Ms. Azza Hashem Al-Zahrani 5. The effect of a proposed unit in science based on PISA standards in developing life problem-solving skills among Prep school students Dr. Naglaa Fauzy Esmaeil Alkest, Prof. Mahmoud Ebrahim Taha, Dr. Mohamed Mostafa Ghalwash